WR A descriptive analysis of entrepreneurial female career success determinants on Saudi Arabia along entrepreneurial process - Ragmoun, wided (Archives of Business Research, 2019)
In this research we aim to identify factors which can contribute to the development of female entrepreneurship. We enumerate these factors in order to stimulate this phenomenon due to its importance for economic development and social development. After identifying these determinants, we list each according to its relative importance and create a matrix, which shows their interdependence at each level of the development of the entrepreneurial process. A quantitative approach was adopted to identify and define these determinants. Our research focused on female entrepreneurial careers in Saudi Arabia. An entrepreneurial career is evaluated as successful if it establishes an entrepreneurial project, because our objective is to motivate women to adopt not only an entrepreneurial intention, but an actual entrepreneurial career. The questionnaire used here was administered to 103 women who had already started an entrepreneurial career. The results show that individual factors are important, but environment factors are more important, especially political factors. The most important contribution of this study is the matrix it defines, in which every determinant can be used differently based on the different steps in the entrepreneurial process. This can provide policy makers with a tool according to which they can detect the key factors of success.